A massive phylloides tumor in the breast: case report and literature review - Wilkinson, T. Raju Vinay; Kashid, Anupama Ashok; Sonarkar, Rajiv Krishnarao (International Surgery Journal, 2020)
Phylloides tumor (PT) is a rare fibro epithelial neoplasm comprising <1% of all breast tumors. Clinical spectrum ranges from benign (B), borderline (BL), and locally recurrent to malignant (M) and metastatic type. Phylloides tumors originate from the connective tissue of the breast, so the malignant phylloides are histologically sarcomas. We are reporting a massive phylloides tumor in a 45 years old female. She presented with a huge breast mass occupying almost the whole of the right breast with two areas of pressure necrosis, on the overlying skin. She noticed a small lump 7 months ago in the right breast, which slowly grew to the current dimensions and areas of pressure necrosis appeared recently. FNAC was reported as a complex fibroadenoma; however due to strong suspicion, a core needle biopsy was done. The report came as a phylloides tumor. Simple mastectomy was done. The tumor specimen measured exactly 20×15×10 cm in size; the histopathology report came as benign phylloides tumor.